Performance of protection devices against transient overvoltage due to lightning: article - Sidin, Mohammad Hafizuddin (2012)
Nowadays, many devices have been developed to overcome transient overvoltage due to lightning strike. This paper presents the performance of protection devices against tran transient over voltages due to lightning strike in a 33/11kV distribution system at UITM Shah Alam. The objective of the project simulation is to compare and analyze the performance of metal oxide varistor (MOV) and transient suppression voltage (TVSS) against indirect lightning effect. The effectiveness of the protection system was tested and compared that implemented in (PSCAD/EMTDC) software. The PSCAD software is a power system simulation that enable problem regarding on the power system be solved. It was found that metal oxide varistor proposed by IEEE model can reduce the surge voltage to the minimum clamp voltage.